Legal Enforcement on Prisoners Escaping from Class IIA Narcotics Correctional Facility, Langkat - Jefri Aritonang; Lidya Rahmadhani Hasibuan; Sidi, Redyanto (PT. Sinergi Legal Publisher, 2026)
The phenomenon of prisoner escapes impacts the criminal law enforcement process, which aims to prevent the public from becoming victims of crime and halt the correctional process in prisons. Sanctions for prisoners who escape from correctional institutions still impose disciplinary penalties in the form of reclusion and the suspension or revocation of certain rights in accordance with applicable laws and regulations without additional criminal proceedings for the inmates. The purpose of this study is to determine law enforcement against prisoners who escaped from correctional institutions, factors that cause prisoners to escape from correctional institutions, and criminal law enforcement against prisoners who escaped from the Class IIA Langkat Narcotics Correctional Institution. This study is a descriptive study with a normative juridical research type using qualitative analysis methods. From the results of the study, the laws and regulations related to prisoners and convicts who escape from detention centers and correctional institutions are Articles 34 and 85 of the Criminal Code, Article 67 of Law Number 22 of 2022 concerning Corrections and Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 6 of 2013 concerning the Rules of Procedure for Correctional Institutions and State Detention Centers, Factors for prisoners escaping from correctional institutions or state detention centers are caused by Internal Factors such as Willingness with personal encouragement, Long prison sentences and External Factors such as Over capacity, Environment and Social Relations, Lack of prison security officers, Inadequate Building Conditions, and Opportunity Factors and Law enforcement against prisoners who escape is by giving sanctions for serious disciplinary violations by entering them into a silent lockup for 12 days and to officers who are negligent or intentionally allow prisoners or detainees to escape is by applying administrative sanctions in the form of warnings to delays in promotions to dismissal from office or with criminal sanctions in prison